First data from a field trial of Quercus suber plants regenerated from mature selected trees and from their half-sib progenies by somatic embryogenesis - Celestino, C.; Hernández, I.; Lopez-Vela, D.; Carneros, E.; Alegre, J.; Toribio, M.; Fernandez-Guijarro, B.; Cardo, L. (Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants, 2007)
Somatic embryogenesis is considered as the most suitable current regeneration technique for the conservation and genetic improvement of tree species. The ability to induce somatic embryogenesis in leaves from mature trees gives the possibility to compare the performance of the parent trees and their progenies at the same age and place of test. Somatic seedlings were regenerated from five selected cork oak trees and from young plants of their half-sib progenies. They were planted in the field conjointly with zygotic seedlings of these families, to test the comparisons somatic vs. zygotic origin and somatic from mature trees vs. somatic from juvenile seedlings. The effect of genotype and kind of progeny will be studied in a complete factorial design; therefore the field trial comprised 15 treatments arranged in five completely randomised blocks. Each experimental unit included three plants that were distributed following a row and column pattern. Fist survival and height data after six and twelve months of establishment are provided. All plants from seeds survived while almost the half of somatic seedlings died after the winter and they were replaced. Almost 70% of these plants survived after the following summer. There were no differences between somatic seedlings of mature or juvenile origin. Zygotic seedlings doubled the height of the somatic ones after one year in the field, and within these plants those of mature origin grew slightly more than those of juvenile source. Differences due to genotype and family effects were noticeable. No apparent morphological alterations were detected among the three kinds of tested progenies.
The following values have no corresponding Zotero field: periodical: Proceedings of the Second International Symposium on Acclimatization and Establishment of Micropropagated Plants issue: 748 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: Cork oak; field establishment; rejuvenation; Somatic embryogenesis; woody plant micro-propagation